Gari: food for the rich or the poor consumers in Nigeria - Meludu, N.; Ajani, O.; Akoroda, M.O. (2004)
The comsumption of garri- a dry granule processed from cassava roots in Nigeria is now a nation-wide habit and practice. Its price fluctuates so much that the question is now being asked as to whom should the commodity be target to? The poor or the rich? This paper reports a study of the faqctors affecting price changes and the determinants of who will in the foreseeable future be able to use the most cherished product form of cassava, a staple food in Nigeria. The preference of this form by consumers of cassava products was examined as it relates to the export of the product as well as its storability. Strategies and theories for a sustained garri economy in rural and urban areas are postulated for Nigeria.